Leishmania infantum released proteins specifically regulate cytokine expression and production patterns by CD4+ and CD8+ T cells - Rosa, Ricardo (2006)
Funding Information: The authors thank J.M. Cristóvão and J. Ramada for technical assistance. Funding for this work was provided by the project research grant POCTI/CVT/37759/2001 by the Fundação para a Ciência e Tecnologia (FCT), Portugal partially supported by the European Union Fund (FEDER), and grant SFRH/BD/997/2000 from FCT.